2022
DOI: 10.1111/vcp.13099
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of procalcitonin and beta‐defensin2 in the serum and feces of dogs with acute diarrhea

Abstract: Background Acute diarrhea is a common clinical condition where clinical parameters are used to assess disease severity, course, and prognosis. Objectives The aim of this study was to investigate procalcitonin (PCT) and beta‐defensin2 (Bdef2) as biomarkers for disease severity, course, and prognosis of dogs with acute diarrhea. Methods Dogs with acute diarrhea (enteritis group [EG], n = 35) were compared with 30 healthy controls. The dogs in the EG were scored using the Canine Acute Diarrhea Severity (CADS) ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…40 In a recent study, prolonged recovery was monitored in dogs with a high PCT level. 22 To the best of our knowledge, no data are available regarding this topic in cats; therefore, we investigated the potential correlation between serum PCT levels measured at the initial admission before the treatment protocol and the mortality rates. The serum PCT levels of cats with bacterial infections that died during the study were higher than those that survived.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 In a recent study, prolonged recovery was monitored in dogs with a high PCT level. 22 To the best of our knowledge, no data are available regarding this topic in cats; therefore, we investigated the potential correlation between serum PCT levels measured at the initial admission before the treatment protocol and the mortality rates. The serum PCT levels of cats with bacterial infections that died during the study were higher than those that survived.…”
Section: Discussionmentioning
confidence: 99%
“…Infectious and non-infectious inflammatory diseases have been reported to result in an increased expression of CALC1, encoding PCT production in dogs. 19,20 Sepsis, 21 bacterial infections 22 and blood parasites 23 increase serum PCT levels. In addition, it has been reported that the PCT level begins to increase 2 h after a lipopolysaccharide injection in dogs, increases significantly over 12 h and returns to baseline after 48 h. 24 To the best of our knowledge, infection-associated PCT production in cats has been documented in a single study, which indicated an increase in serum PCT levels during bacterial infections.…”
Section: Introductionmentioning
confidence: 99%
“…Acute diarrhea is one of the most frequently reported daily complaints in a small animal veterinary clinic. It only rarely reveals a specific etiology, and the clinical presentation is extremely variable, ranging from uncomplicated cases (acute uncomplicated diarrhea—AUD) to life-threatening ones [ 1 ]; consequently, the therapy is also extremely variable and mostly based on symptomatic/supportive (seldomly etiologic) therapy, depending on the severity of the clinical signs and on the presence/absence of comorbidities [ 2 , 3 , 4 ]. Little is known about what happens in the gastrointestinal lumen/mucosa during acute diarrhea in living subjects [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the focal purposes of proteomics, there is the discovery of biomarkers to be applied for diagnostic/monitoring purposes, and more in general for a better understanding of the pathophysiology of determined conditions in specific biological environments. There is a growing interest in the search for new biomarkers useful in the diagnosis, course evaluation, and prognosis of patients with acute diarrhea [ 1 , 5 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diarrhoea is a primary symptom of intestinal disorders and characterized by alterations in faecal fluidity, volume and frequency of defecation (Nixon et al., 2019). The major pathological conditions affecting the intestines are those that cause structural mucosal damage and result in decreased mucosal surface area (Allenspach & Gaschen, 2008; Allenspach et al., 2007), which are caused by infectious (viruses, bacteria and parasites) and non‐infectious (sudden diet change, food intolerance, irritable bowel syndrome and inflammatory bowel disease (IBD), such as ulcerative colitis and hyperthyroidism) factors (Candellone et al., 2020; Neumann et al., 2022).…”
Section: Introductionmentioning
confidence: 99%